Algebraic topology - Sato, Hajime (American Mathematical Society, 1999)
Homeomorphisms and homotopy equivalences -- Topological spaces and cell complexes -- Homotopy -- Homology -- Homology groups of cell complexes -- Cohomology -- The universal coefficient theorem -- Fiber bundles and vector bundles -- Spectral sequences.; Includes bibliographical references (p. 115-116) and index